MICROCONTROLLER BASED SOLAR POWERED AUTOMATIC STREET LIGHT INTENSITY CONTROLLER - Jain, Urja; Jain, Anindya; Shukla, Deepali (Innovare Journal of Engineering and Technology, 2018)
Objective: The main purpose of this paper is to design and execute the system to control the intensity of the street light without any manual operation. Methods: The system is based on the principle of light and motion sensing. The system is made efficient enough by replacing the HID lamps with the LEDs. In general, street lights on the highways are designed with high-intensity lamps that consume more energy and also cannot be changed as per the requirement. Thus, the proposed system overcomes these problems using LEDs instead of HID lamps in the street light systems. It is the Dual Power Saver setup since it saves power with the help of solar energy which charges the battery of the circuit using the solar panel and second by just increasing the intensity of the LED in the presence of a pedestrian or a vehicle using the suitable combination of microcontroller and IR sensors. The Microcontroller AT89c51 is used for control mechanism of the system. Results and Conclusion: The smart street light control system adopts a dynamic control methodology. According to the proposed plan, initially, when it becomes dark, all the street lights automatically glows with low intensity. However, throughout the night streetlights remain switched on for security concerns on low intensity. When a vehicle passes by, a block of street lights glows, and as the vehicle moves forward, the next block of lights starts glowing where the previous block switches back to low intensity. Whereas, lights will be kept OFF when there is sufficient amount of natural light is available. The proposed work would help in reducing the overall consumption of street light energy and support to energy-saving aspects of the nations.